NEW EMBO MEMBERS’ REVIEW: Entry of ricin and Shiga toxin into cells: molecular mechanisms and medical perspectives - Sandvig, K. (Oxford University Press, 2000)
A large number of plant and bacterial toxins with enzymatic activity on intracellular targets are now known. These toxins enter cells by first binding to cell surface receptors, then they are endocytosed and finally they become translocated into the cytosol from an intracellular compartment. In the case of the plant toxin ricin and the bacterial toxin Shiga toxin, this happens after retrograde transport through the Golgi apparatus and to the endoplasmic reticulum. The toxins are powerful tools to reveal new pathways in intracellular transport. Furthermore, knowledge about their action on cells can be used to combat infectious diseases where such toxins are involved, and a whole new field of research takes advantage of their ability to enter the cytosol for therapeutic purposes in connection with a variety of diseases. This review deals with the mechanisms of entry of ricin and Shiga toxin, and the attempts to use such toxins in medicine are discussed.